The physical health of Indigenous and non-Indigenous patients participating in residential rehabilitation programs: a comparison study. (April 2017) - Meehan, Tom; Jones, Donna; Stedman, Terry; Johnson, Dean; Suetani, Shuichi; Foreman, Emma
Objective: To examine the differences in the physical health of Indigenous and non-Indigenous patients with severe mental illness (SMI) undergoing psychiatric rehabilitation. Methods: An audit of the physical health of patients ( n = 361) in all publicly funded residential rehabilitation programs in Queensland was carried out in late 2014. Data collection focused on clinical and lifestyle factors associated with physical health. Results: The prevalence of smoking, substance use and type 2 diabetes in Indigenous patients was significantly higher than rates found in non-Indigenous patients. Metabolic syndrome was also significantly higher in indigenous patients, with 66% of Indigenous patients compared to 46% of non-Indigenous patients meeting criteria for metabolic syndrome. Conclusions: Patients with SMI in residential rehabilitation programs have poor physical health. Our findings underscore the need for clinicians to develop and evaluate interventions aimed at improving the metabolic profile of those with SMI in residential rehabilitation programs. Historical factors and cultural traditions need to be considered when designing lifestyle interventions for Indigenous patients.